Progressive Familial Intrahepatic Cholestasis - A Case Report - Begum, Nazma; Karim, ASM Bazlul (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v33i2.5685 Bangladesh Journal of Child Health 2009; Vol.33(2): 66-69